Identification of Candidate Genes Responsible for Flower Colour Intensity in Gentiana triflora - Tasaki, Keisuke; Watanabe, Aiko; Nemoto, Keiichirou; Takahashi, Shigekazu; Goto, Fumina; Sasaki, Nobuhiro; Hikage, Takashi; Nishihara, Masahiro (Frontiers in Plant Science, 2022)
Gentians cultivated in Japan (Gentiana triflora and G. scabra and hybrids) have blue flowers but flower colour intensity differs among cultivars. The molecular mechanism underlying the variation in flower colour intensity is unclear. Here, we produced F2 progeny derived from an F1 cross of intense- and faint-blue lines and attempted to identify the genes responsible for flower colour intensity using RNA-sequencing analyses. Comparative analysis of flower colour intensity and transcriptome data revealed differentially expressed genes (DEGs), although known flavonoid biosynthesis-related genes showed similar expression patterns. From qRT-PCR analysis, we identified two and four genes with significantly different expression levels in the intense- and faint-blue flower lines, respectively. We conducted further analyses on one of the DEGs, termed GtMIF1, which encodes a putative mini zinc-finger protein homolog, which was most differently expressed in faint-blue individuals. Functional analysis of GtMIF1 was performed by producing stable tobacco transformants. GtMIF1-overexpressing tobacco plants showed reduced flower colour intensity compared with untransformed control plants. DNA-marker analysis also confirmed that the GtMIF1 allele of the faint-blue flower line correlated well with faint flower colour in F2 progeny. These results suggest that GtMIF1 is one of the key genes involved in determining the flower colour intensity of gentian.